The effect of fractional inspired oxygen concentration on early warning score performance: A database analysis. (June 2019) - Malycha, James; Farajidavar, Nazli; Pimentel, Marco A.F.; Redfern, Oliver; Clifton, David A.; Tarassenko, Lionel; Meredith, Paul; Prytherch, David; Ludbrook, Guy; Young, J.Duncan; Watkinson, Peter J.
Abstract: Objectives: To calculate fractional inspired oxygen concentration (FiO2 ) thresholds in ward patients and add these to the National Early Warning Score (NEWS). To evaluate the performance of NEWS-FiO2 against NEWS when predicting in-hospital death and unplanned intensive care unit (ICU) admission. Methods: A multi-centre, retrospective, observational cohort study was carried out in five hospitals from two UK NHS Trusts. Adult admissions with at least one complete set of vital sign observations recorded electronically were eligible. The primary outcome measure was an 'adverse event' which comprised either in-hospital death or unplanned ICU admission. Discrimination was assessed using the Area Under the Receiver Operating Characteristic curve (AUROC). Results: A cohort of 83, 304 patients from a total of 271, 363 adult admissions were prescribed oxygen. In this cohort, NEWS-FiO2 (AUROC 0.823, 95% CI 0.819–0.824) outperformed NEWS (AUORC 0.811, 95% CI 0.809–0.814) when predicting in-hospital death or unplanned ICU admission within 24 h of a complete set of vital sign observations. Conclusions: NEWS-FiO2 generates a performance gain over NEWS when studied in ward patients requiring oxygen. This warrants further study, particularly in patients with respiratory disorders.